FAMILY PROFESSIONALS’ ATTITUDES AND STANCE-TAKING ON POST-DIVORCE FATHERHOOD: A QUALITATIVE ATTITUDE APPROACH - Autonen-Vaaraniemi, Leena (International Journal of Child, Youth and Family Studies, 2022)
This article examines divorce professionals’ attitudes and stances in response to common criticisms of how they deal with divorce outcomes for fathers, according to which men are discriminated against in negotiations on the custody and living arrangements of their children. The study applied the relatively new qualitative attitude approach, and hence a further aim was to test its fitness for studying attitudes. Eighteen Finnish family professionals who worked with divorce cases — social workers, psychologists, district court judges, and lawyers — participated in semi-structured interviews in which they discussed claims designed to be provocative. The family professionals were found to show both collective, shared attitudes and diversity in attitudes and stances. The participants strove to position themselves as gender-neutral and as promoters of equality between mothers and fathers, and thus in accordance with the ideal of a good professional. The divorce professionals argued that their overriding aim was to secure the well-being of children. The method revealed some attribution bias, manifested as victim blaming, where fathers themselves were in part held accountable for the gendered post-divorce situation. The results highlight potential areas of cooperation between different types of divorce professionals that could lay a foundation for improving services and support for divorced parents and children.